Government bond liquidity and sovereign-bank interlinkages - Sören Radde; Cristina Checherita-Westphal; Wei Cui (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Banks in the euro area typically hold a large amount of government debt in their bond portfolios, which are valued both for their low credit risk and high liquidity. During the sovereign debt crisis, these characteristics of government debt were severely impaired in stressed euro area countries. In order to understand the transmission channels of stress from government debt markets to the real economy, we augment a standard dynamic macroeconomic model with a banking sector and a market for government debt characterized by search frictions. A sovereign solvency shock modelled as a haircut on government bonds is introduced to study the interaction of sovereign credit and liquidity risk. As banks react to this shock by rebalancing towards highly liquid short-run assets, such as central bank deposits, demand for government bonds collapses, which endogenously worsens their market liquidity. Thus, a sovereign liquidity risk channel from government bond markets to the real sector emerges. Endogenous government bond liquidity negatively affects the funding conditions of the fiscal sector, tightens financing constraints in the banking sector and lowers investment and output. The model is able to match a number of stylised facts regarding the behaviour of sovereign debt markets during the euro area sovereign debt crisis, such as depressed turnover rates and rising bid-ask spreads.
Keywords: 330; liquidity frictions; search; sovereign risk channel; sovereign-bank nexus